2018
DOI: 10.1016/j.cobeha.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Functions of medial hypothalamic and mesolimbic dopamine circuitries in aggression

Abstract: Aggression is a crucial survival behavior: it is employed to defend territory, compete for food and mating opportunities, protect kin, and resolve disputes. Although widely differing in its behavioral expression, aggression is observed across many species. The neural substrates of aggression have been investigated for nearly a century and two highly conserved circuitries emerge as critical substrates for generating and modulating aggression. One circuitry centers on the medial hypothalamus. Activity of the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 88 publications
(78 reference statements)
0
29
0
Order By: Relevance
“…Finally, recent studies reported roles of other cell-typespecific circuits in aggression reward, as assessed in the selfadministration and CPP procedures (Aleyasin et al, 2018a;Yamaguchi and Lin, 2018). These include estrogen-receptor ␣1expressing neurons of ventromedial hypothalamus (Falkner et al, 2016), dopamine transporter-expressing neurons of hypothalamic ventral premammillary nucleus projecting to supramammillary nuclei (Stagkourakis et al, 2018), and GABAergic projections from basal forebrain to lateral habenula (Golden et al, 2016).…”
Section: Appetitive Aggression Reward In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, recent studies reported roles of other cell-typespecific circuits in aggression reward, as assessed in the selfadministration and CPP procedures (Aleyasin et al, 2018a;Yamaguchi and Lin, 2018). These include estrogen-receptor ␣1expressing neurons of ventromedial hypothalamus (Falkner et al, 2016), dopamine transporter-expressing neurons of hypothalamic ventral premammillary nucleus projecting to supramammillary nuclei (Stagkourakis et al, 2018), and GABAergic projections from basal forebrain to lateral habenula (Golden et al, 2016).…”
Section: Appetitive Aggression Reward In Rodentsmentioning
confidence: 99%
“…We focused on the nucleus accumbens (NAc), which earlier research has implicated in aggression self-administration and CPP (Couppis and Kennedy, 2008;Golden et al, 2016;Aleyasin et al, 2018b). There has been a recent interest in the role of the mesolimbic dopaminergic circuit in controlling aggression reward (Flanigan et al, 2017;Aleyasin et al, 2018a;Yamaguchi and Lin, 2018), as dopaminergic projections from the ventral tegmental area (VTA) to the NAc modulate both aggression intensity (Yu et al, 2014) and NAc dopamine levels Miczek, 2000, 2007). Additionally, local dopamine receptor blockade decreases aggression-reinforced operant responding (Couppis and Kennedy, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of other brain regions express androgen receptors and are associated with aggression are not included in this review such as the medial amygdala (Clinard et al, 2016) and ventromedial hypothalamus (Falkner et al, 2016). Most work on amygdala and hypothalamic modulation of aggression focuses primarily on intensity of aggression rather than other aspects of territoriality (Kruk et al, 1998;Yamaguchi and Lin, 2018). Below we highlight specific brain regions that link rewarding aspects of T, association of T with site fidelity and the vigilance needed to protect offspring and the territory.…”
Section: Social Vigilance a Mechanism For Deciding To Engagementioning
confidence: 99%
“…The hypothalamus is strongly linked with aggression, due to the depth of cross-species experiments and pan-methodological approaches repeatedly attributing the initiation of aggression to its subnuclei. Termed the hypothalamic attack area, this region classically spans the lateral through ventromedial hypothalamus, and has been the focus of aggression research for decades (Siegel et al, 1999;Hashikawa et al, 2017b;Yamaguchi and Lin, 2018). Recent work by Lin and colleagues (Lin et al, 2011;Falkner et al, 2014;Hashikawa et al, 2017a) has more selectively identified Esr1 ϩ neurons within the ventrolateral portion of the ventromedial hypothalamus (VMHvl) as the critical population controlling the initiation of aggression in both male and female mice.…”
Section: Neuroanatomical Mechanismsmentioning
confidence: 99%
“…Due to space limitations, we do not describe results from recent studies in which cell-type and circuit-specific optogenetic and chemogenetic methods were used to elicit unconditioned aggressive behavior in different brain areas. We refer the readers to excellent recent reviews on this topic, which provide overviews summarizing these brain regions and circuits (Miczek et al, 2015;Aleyasin et al, 2018a;Yamaguchi and Lin, 2018;Flanigan and Russo, 2019).…”
Section: Introductionmentioning
confidence: 99%